Modeling the stream temperature regime of the East Fork of the Virgin River in Zion National Park - Peterson, Karen L., author; Sanders, Thomas G., advisor; Hendricks, David W., committee member; Parce, Stanley L., committee member; Ward, Robert C., committee member (Colorado State University. Libraries, 1991)
The following stream temperature study was conducted as part of a general study by the Water Rights Branch, Water Resources Division, National Park Service, to evaluate the physical habitat of the aquatic organisms within Zion National Park (ZION). Stream temperature is an aquatic habitat characteristic that is known to be a controlling variable in the successful existence of the Virgin spinedace (Espinosa, 1978). The Virgin River spinedace, a non-game fish which is endemic to the East Fork of the Virgin River, was delineated as the target organism as it has been recommended for classification as threatened (50 F.R. 37959). The first objective of the study was to measure and describe existing stream temperatures of the East Fork of the Virgin River at Virgin River Mile (VRM) 157.3. Diurnal fluctuations in the stream temperature of 10°C were common. The average maximum, mean, and minimum stream temperatures for the study period were 26.7°C, 21.8°C, and 17.0°C, respectively during which the average flow was 1076 l/s. A second objective of the study was to predict the response of the daily fluctuations and mean daily stream temperature at VRM 157.3 to perturbations in stream temperature and discharge at the upstream (eastern) Zion National Park boundary. Stream, shading, and site characteristic data were collected along a 9.3 km reach on the East Fork and input into TEMP-84, a stream temperature model, for simulation of existing and perturbed flows of 283 l/s (10 cfs), 566 l/s (20 cfs), 2,124 l/s (75 cfs), 2,832 l/s (100 cfs), 14,160 l/s (500 cfs), and 28,320 l/s (1000 cfs). Perturbed inflow temperature conditions were delineated as equal to the average ambient temperature and groundwater temperature. Modeled results were evaluated in terms of the relative change in maximum, mean, and minimum stream temperature from that modeled for existing conditions. The relative change was then applied to measured stream temperatures to estimate stream temperatures for the selected hypothetical condition. Results from the modeling exercise demonstrated sharply dampened diurnal fluctuations at VRM 157.3 from an average of 10.1°C under existing conditions to 4.7°C as the flow increased to 2,832 l/s. As the flow was increased beyond 2,832 l/s, the diurnal fluctuation at VRM 157.3 decreases further and approached that of VRM 163.1 at the upstream end of the study reach. Mean stream temperatures at VRM 157.3 decreased by an average of 2.4°C as the flow increased to 14,160 l/s. Flows less than baseflow simulated dramatically increased diurnal fluctuations; diurnal fluctuations of 17.3°C were simulated for flows of 283 l/s. Mean stream temperatures increased by an average of 1.5°C when inflow was decreased to 283 l/s. Hypothetical inflow temperature simulations depicted a clear shift in the diurnal fluctuation at VRM 157.3 in the direction of the change in inflow stream temperature at VRM 163.1. Mean stream temperatures increased by an average of 4.6°C when inflow was equal to the average ambient temperature and decreased by an average of 2.0°C when inflow was equal to groundwater temperature.
Keywords: Water temperature -- Mathematical models; Virgin River -- Temperature